Self-Objectification dan Body Shame pada Perempuan Dewasa Awal - Ciutarno, Novia; Pesau, Heni Gerda (Journal of Indonesian Psychological Science (JIPS), 2024)
Changes in interest about appearance and social roles made women in early adulthood begin to feel anxious about living in a new environment and trigger the possibility of experiencing objectification from others. Women who internalize this objectification will experience self-objectification which can cause body shame when their body does not meet the ideal beauty standards. This research aims to analyze the relationship between self-objectification and body shame of women in early adulthood. This study involved 150 women in early adulthood aged 20 to 30 years and domiciled in Makassar City. This research used quantitative methods with self-objectification and body shame scales as research measurement tools and analyzed by Pearson Product Moment. The result of this research showed a significance value of 0.000 and a correlation value of 0.297, which means that there is a positive relationship between self-objectification and body shame of women in early adulthood. KEY WORDS: body shame; self-objectification; women in early adulthood